A transaction-cost approach to enterprise modeling and coordination between small growers and a large firm: The case of mussel mariculture in South Africa - Karaan, A.S. Mohammad (International Food Policy Research Institute, 2009)
The challenge of growing the agricultural sector in South Africa entails, among other things, the creation of livelihoods for previously disadvantaged farmers by facilitating their integration into established farming. It is argued that small start-up firms face considerable transaction costs in commencing business and establishing business relations with dominating large firms, even though small-scale farming brings significant efficiency gains (principally by the use of family labor), which suggests that small firms should dominate this industry.